The Effect of Organizational Culture, Transformational Leadership and Organizational Environment to the Organizational Commitment and Performance of Private Higher Performance in East Kalimantan Province - Sugiono Sugiono; Ida Ayu Brahmasari; I Dewa Ketut Raka Ardiana (Sebelas Maret Business Review, 2019)
This study aims to analyze the influence of organizational culture, transformational leadership and organizational environment on organizational commitment and performance. 200 responses were collected through surveys gathered from 8 Universities, 34 High School and 15 Academy. Data were analyzed using Structural Equation Model (SEM) and found that the organizational culture, transformational leadership, and organizational environment has a significant effect on organizational commitment and performance of Private Higher Education in East Kalimantan Province except organizational environment has no significant effect on the performance of Private University in East Kalimantan Province. Organizational commitment variable can be a variable that can improve the effect of organizational culture, transformational leadership and organizational environment on the performance of Private Universities in East Kalimantan Province.